Structural Reforms and Productivity Growth in Emerging Market and Developing Economies - Dabla-Norris, Era (IMF Working Papers; Working Paper, 2016)
This paper empirically assesses the role of structural and institutional reforms in driving productivity growth across countries at different stages of development, using a distance-to-frontier framework. It gauges whether particular policies and reforms matter more for increasing productivity growth at the aggregate and sectoral levels for some emerging market and developing economies (EMDEs) than others. Recognizing the possibility of time lags between reform implementation and reform payoffs, the paper also examines how productivity gains from various reforms evolve over the the short- and medium-term.